MUMBAI - Rosengaard, Camilla (Tidsskriftet Antropologi, 2003)
The last ten years of growth in the Indian economy has nurtured dreams of the ‘good life’ among both the rich and the poor in the city of Mumbai (Bombay). The city and the home are important scenes in which the realizations of this metropolis’ 16 million inhabitants are played out. Whilst the middle classes, to an ever growing extent, realize dreams of the good life, inspired by the tranquil suburban life of the Western middle-class, the underclass must employ other life strategies in their attempt to turn dreams into reality.